An in vitro Comparison of Bond Strength of Different Sealers/Obturation Systems to Root Dentin Using the Push-Out Test at 2 Weeks and 3 Months after Obturation - Yap, W.Y.; Che Ab Aziz, Zeti Adura; Azami, N.H.; Al-Haddad, A.Y.; Khan, A.A. (Karger Publishers Open Access, 2017)
Objective: To evaluate the push-out bond strength and failure modes of different sealers/obturation systems to intraradicular dentin at 2 weeks and 3 months after obturation compared to AH Plus®/gutta-percha. Materials and Methods: A total of 180 root slices from 60 single-canal anterior teeth were prepared and assigned to 5 experimental groups (n = 36 in each group), designated as G1 (AH Plus®/gutta-percha), G2 (TotalFill BC™ sealer/BC-coated gutta-percha), G3 (TotalFill BC™ sealer/gutta-percha), G4 (EndoREZ® sealer/EndoREZ®-coated gutta-percha), and G5 (EndoREZ® sealer/gutta-percha). Push-out bond strengths of 18 root slices in each group were assessed at 2 weeks and the other 18 at 3 months after obturation using a universal testing machine. Data were analyzed using repeated measures ANOVA. An independent t test was used to compare the mean push-out bond strength for each group at 2 weeks and 3 months after obturation. Results: The mean push-out bond strengths of G4 and G5 were significantly lower than those of G1, G2, and G3 (p < 0.05) at both 2 weeks (G1: 1.46 ± 0.29 MPa, G2: 1.74 ± 0.43 MPa, G3: 1.74 ± 0.43 MPa, G4: 0.66 ± 0.31 MPa, G5: 0.74 ± 0.47 MPa) and 3 months after obturation (G1: 1.70 ± 1.05 MPa, G2: 3.69 ± 1.20 MPa, G3: 2.84 ± 0.83 MPa, G4: 0.14 ± 0.05 MPa, G5: 0.24 ± 0.10 MPa). The mean push-out bond strengths of G2 (3.69 ± 1.20 MPa) and G3 (2.84 ± 0.83 MPa) were higher at 3 months compared to 2 weeks after obturation (G2: 1.74 ± 0.43 MPa, G3: 1.33 ± 0.29 MPa). Conclusion: The TotalFill BC™ obturation system (G2) and the TotalFill BC™ sealer/gutta-percha (G3) showed comparable bond strength to AH Plus®. Their bond strength increased over time, whereas the EndoREZ® obturation system (G4) and EndoREZ sealer (G5) had low push-out bond strength which decreased over time.